Google and the culture of search - Hillis, Ken.; Petit, Michael; Jarrett, Kylie (New York ; London : Routledge, 2013)
"Google and the Culture of Search examines the role of search technologies in shaping the contemporary digital and informational landscape. Ken Hillis and Michael Petit shed light on a culture of search in which our increasing reliance on search engines like Google, Yahoo! and Bing influences the way we navigate Web content--and how we think about ourselves and the world around us, online and off. Even as it becomes the number one internet activity, the very ubiquity of search technology naturalizes it as utilitarian and transparent--an assumption that Hillis and Petit explode in this innovative study. Commercial search engines supply an infrastructure that impacts the way we locate, prioritize, classify, and archive information on the Web, and as these search functionalities continue to make their way into our lives through mobile, GPS-based platforms and personalized results, distinctions between the virtual and the real collapse. Google--a multibillion-dollar global corporation--holds the balance of power among search providers, and the biases and individuating tendencies of its search algorithm undeniably shape our collective experience of the internet and our assumptions about the location and value of information. Google and the Culture of Search explores what is at stake for an increasingly networked culture in which search technology is a site of knowledge and power. This comprehensive study of search technology's broader implications for knowledge production and social relations is an indispensable resource for students and scholars of Internet and new media studies, the digital humanities, and information technology. "--
Includes bibliographical references and index.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2020. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Google; Web search engines -- Social aspects; Internet searching -- Social aspects; Internet users -- Psychology; Information technology -- Social aspects; Electronic books